ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PT JAPFA COMFEED INDONESIA TBK (2019-2021) - ,; , (Bilancia : Jurnal Ilmiah Akuntansi; Vol 7 No 2 (2023): Bilancia : Jurnal Ilmiah AkuntansiDO - 10.35145/bilancia.v7i2.2204, 2023)
ABSTRACT This research was conducted on PT Japfa Comfeed Indonesia Tbk, which is one of the largest agri-food industries in Indonesia. The purpose of this study is to assess the financial performance of PT Japfa Comfeed Indonesia Tbk for the period 2019-2021. The research method used is descriptive quantitative and research instruments obtained from the annual financial statements. In measuring financial performance, liquidity ratio analysis is used which includes Quick Ratio, Cash Ratio, and Current Ratio, as well as profitability ratios which include NPM, ROA, and ROE. From the results of the review, it was found that the financial performance of the organization in 2019-2021 was categorized as tending to be unhealthy in terms of its liquidity ratio, only the current ratio in 2021 was categorized as quite healthy because the ratio was right at the industry average standard. Meanwhile, in terms of profitability ratios, it is also categorized as unhealthy because it is still far from the industry average standard, as a result it can be seen that the organization is still not ideal in creating profits. Keywords: Financial Performance, Liquidity, Profitability ABSTRAK Penelitian ini dilakukan terhadap perusahaan PT Japfa Comfeed Indonesia Tbk yang merupakan satu dari industri agri-food terbesar di Indonesia. Tujuan pada penelitian ini untuk menilai kinerja keuangan PT Japfa Comfeed Indonesia Tbk periode 2019-2021. Metode penelitian yang dipakai ialah deskriptif kuantitatif serta instrument penilitian yang diperoleh dari laporan keuangan tahunan. Dalam pengukuran kinerja keuangan dipergunakan analisis rasio likuiditas yang mencakup Quick Ratio, Cash Ratio,dan Current Ratio, juga rasio profitabilitas yang mencakup NPM, ROA, dan ROE. Dari hasil peninjauan tersebut didapatkan kinerja keuangan organisasi tersebut pada tahun 2019-2021 dikategorikan cenderung tidak sehat dari segi rasio likuiditasnya, hanya Current ratio tahun 2021 yang dikategorikan cukup sehat karena rasionya tepat pada standar rata-rata industri. Sedangkan dari segi rasio profitabilitas juga dikategorikan cenderung tidak sehat karena masih jauh dari standar rata-rata industri, akibatnya dapat terlihat bahwa organisasi masih belum ideal dalam menciptakan laba. Kata kunci: Kinerja Keuangan, Likuiditas, Profitabilitas